Pomegranate 5 (August 1998) - (:unkn) unknown (The Pomegranate, 1998)
Recent Developments in the Study of the Great European Witch Hunt / by Jenny Gibbons -- The Interface of Archaeology and Mythology: A Philosophical Evaluation of the Gimbutas Paradigm / by Mara Keller -- Asherah: Goddess of the Israelites / bt Fritz Muntean -- The Rose Beyond the Grave / Evan John Jones -- Book Reviews: Two Roads to Magical Herbalism: A Compendium of Herbal Magick by Paul Beyerl / reviewed by Chas S. Clifton ; Psychedelic Shamanism by Jim DeKorne / reviewed by Chas S. Clifton
The Pomegranate: A New Journal of Neopagan Thought
1 Electronic record(s) and derivatives. PDF file. 30 pages. 368072 bytes.
Keywords: Periodicals; Witch hunting--Europe--History; Gimbutas, Marija, 1921-1994--Criticism and interpretation; Asherah (Semitic deity)--History; Roses--Symbolic aspects; Beyerl, Paul V., Rev., 1945- Compendium of herbal magick--Reviews; DeKorne, Jim. Psychedelic shamanism--Reviews; Book reviews; Literary criticism